The inflow performance relationship in fractured, vertical, and dewatered coalbed-methane wells - Dou, Xiangji; Lu, Jiahao; Li, Jingxuan; Wu, Xiaojun; Zhai, Yu; Wu, Bo; Qian, Kun (Frontiers in Earth Science, 2022)
Although not greatly studied, the inflow performance relationship (IPR) in dewatered and vertical coalbed methane (CBM) wells is essential in the development of a CBM reservoir. The dynamics of the stress sensitivity effect (SSE) and the matrix shrinkage effect (MSE), as well as the hydraulic fracture propagation, have all been neglected, especially for the exterior region, which is larger than the drainage radius. A novel IPR model has now been built that integrates dynamic SSE–MSE and hydraulic fracture propagation into the skin factor, and is validated with real production data from the Qinshui Basin, China. The absolute open flow rate given the SSE–MSE is 60.5% larger than without SSE–MSE. If the positive effect of the SSE–MSE on the permeability in the exterior region is neglected, the absolute open flow rate is reduced by 21%. The MSE has a greater effect on the fracturing skin factor than the SSE and tends to lower the fracturing skin factor, benefitting the production of CBM. Moreover, in light of the SSE or MSE, the non-Darcy flow effect is weaker due to restraints on the velocity of flow or the permeability. Useful and essential theoretical guidance for real CBM production can thus be gleaned from this novel IPR model.